Inhibition of inflammasome activation improves lung acute injury induced by carrageenan in a mouse model of pleurisy. Issue 8 (19th September 2017) - Fusco, Roberta; Gugliandolo, Enrico; Biundo, Flavia; Campolo, Michela; Di Paola, Rosanna; Cuzzocrea, Salvatore
ABSTRACT: The inflammasome NLRP3 is a molecular pathway activated by a wide range of cellular insults to elicit innate immune defenses through the activation of caspase‐1 and the maturation of proinflammatory cytokines, such as IL‐1β and IL‐18. The expression of NRLP3 is abnormally elevated in numerous human inflammatory diseases, including pulmonary diseases. An injection of carrageenan (CAR) into the pleural cavity triggered an acute inflammatory response, leading to tissue damage, inflammatory exudates, leukocyte infiltration, and increased myeloperoxidase activity. The aim of this study was to assess the effect of the inflammasome blocking agents BAY 11–7082 (30 mg/kg, i.p.) and Brilliant Blue G (BBG) (45.5 mg/kg, i.p.) in a mouse model of CAR‐induced pleurisy. Treatment with BAY 11–7082 or BBG 1 h after CAR injection attenuated pulmonary membrane thickening and polymorphonuclear leukocyte infiltration, reduced NF‐kB translocation in the nucleus, and inhibited the assembly of the NRLP3/ASC/caspase‐1 complex. Treatment with BAY 11–7082 or BBG also down‐regulated iNOS, nitrotyrosine, and poly‐ADP‐ribosyl polymerase expression and inhibited CAR‐induced apoptosis. Our results demonstrate that treatment with inflammasome‐blocking agents can significantly reduce the development of acute CAR‐induced lung injury.—Fusco, R. Gugliandolo, E., Biundo, F., Campolo, M., Di Paola, R., Cuzzocrea, S. Inhibition of inflammasome activation improves lung acute injury induced by carrageenan in a mouse model of pleurisy. FASEB J . 31, 3497–3511 (2017). www.fasebj.org